THE EFFECTIVENESS OF INTERACTIVE LEARNING MEDIA IN IMPROVING STUDENT PARTICIPATION AND LEARNING OUTCOMES IN SENIOR HIGH SCHOOLS - Aribuma, Akhmar; Listiani, Elis; Hidayana, Fahmi Nur; Febianto, Ricky; Melisa, Riri Citra; Siwananda, Niluh Asti Yonanta (Jurnal Penelitian Pendidikan Indonesia, 2025)
Interactive learning, which utilizes technology to encourage collaborative interaction, is increasingly gaining attention as a strategy to increase student engagement and learning outcomes. This research investigates the effectiveness of interactive learning media in increasing the participation and academic achievements of High School (SMA) students. Using a descriptive qualitative approach, this study analyses various sources of literature, scientific articles, and relevant journals to examine the relationship between interactive learning and improving the learning outcomes of high school students. A comprehensive analysis of the existing literature shows a positive correlation between using interactive learning media and increased student active participation in the learning process. Students involved in interactive learning show an increased understanding of concepts, problem-solving, and critical thinking skills. In addition, interactive media is also proven to accommodate various learning styles, thus creating an inclusive and effective learning environment for all students. This finding highlights the importance of technology integration in learning in high school to create a more interesting, practical, and student-centered learning experience. Further research is recommended to quantitatively measure the impact of interactive learning on student learning outcomes in various contexts and subjects in high school. Interactive learning has great potential to improve the quality of high school education and prepare students to face the challenges of the 21st century.